Determination of Optimized Mix Design of Reactive Powder Concrete - Abbas Moslehi; Mohammad Ali Dashti Rahmatabadi; Hosein Arman (Advances in Civil Engineering, 2023)
There are different types of reactive powder concrete (RPC) and researchers continue to develop better-quality mix designs. This research presents an integrated approach for RPC mix design. For this purpose, 13 RPC mix designs were collected according to expert opinion and laboratory samples and were tested in this study for validation of the characteristics of compressive strength and water absorption. The samples were then ranked using the simple additive weighting (SAW) method, and three highest-quality RPCs were selected for the Taguchi method. These RPCs were used to prepare 27 experimental RPC mix designs applying the Taguchi method. From the experimental results, compressive strength with 0.38–0.76% and water absorption with 0.50–0.99% differences were more appropriate in compliance with the collected data. Also, results from the 27 mix designs investigated by the Taguchi method revealed the optimized mix design for the maximum compressive strength with 146.7 MPa and the optimized mix design for the minimum water absorption with 0.89%. The results showed that our approach was consistent with the results of classic methods that require a large number of samples. This suggests that integrating the SAW and Taguchi methods is an appropriate approach for screening and optimizing RPC mix design.